Value of Fungicide Application in Wheat Production in Southwest Kansas, 2017 Report - A. J. Foster; R. Lollato; M. Vandeveer; E. D. De Wolf; R. Currie (Kansas Agricultural Experiment Station Research Reports, 2018)
During the past several years, applying fungicide to wheat has become a more common practice. The availability of cost-effective generic fungicides, as well as the positive yield responses often reported, seem to be the potential drivers for the adoption of such practices by producers. A wheat fungicide trial was conducted in Garden City, KS, to answer the following questions: 1) Are fungicide applications profitable? and 2) Can remote sensing technology be used to quantify the efficacy of different fungicide products? The study consisted of two wheat varieties sown on September 30, 2016 (Oakley CL, highly resistant to stripe rust; and TAM 111, highly susceptible to stripe rust) and treated with different fungicide products. Stripe and leaf rust were the major fungal diseases impacting wheat yield in southwest Kansas in 2017. Wheat production in 2017 was impacted by dry planting conditions in late 2016, a winter ice storm in January, and a late snow storm on April 30, and severe wheat streak mosaic virus infestation. There were significant differences in grain yield among fungicide products for both TAM 111 and Oakley CL. The large changes in normalized difference vegetation index (NDVI) values suggest that multiple environmental factors were interacting to impact the wheat plant health. The benefit of fungicide application observed on yield was minimal under the environmental conditions of 2017.
Keywords: fungicide application in wheat; wheat production in southwest Kansas; value of fungicide